2012
DOI: 10.1080/08946566.2011.646512
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Abuse of Older Adults: What We Know, What We Need to Know

Abstract: Although Canadian policies support "aging in place," there still will be a number of older adults who will require institutional care in the future. Most research on elder abuse, however, has focused on domestic abuse and has paid less attention to institutional abuse. The purpose of this article is to comprehensively review current research to identify gaps in knowledge and methodological issues in the study of institutional abuse. Overall, 49 studies in English and 20 studies in French were reviewed, and 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 48 publications
1
78
0
1
Order By: Relevance
“…Raja, 2005;Carr et al, 2010;McDonald et al, 2012). This research has begun to uncover at least two important patterns.…”
Section: Jennifer J Freydmentioning
confidence: 99%
“…Raja, 2005;Carr et al, 2010;McDonald et al, 2012). This research has begun to uncover at least two important patterns.…”
Section: Jennifer J Freydmentioning
confidence: 99%
“…Difficulties in estimating prevalence and incidence of institutional elder abuse is referred in various studies, 6,14,15 with underreport being the justification found for this fact. 1,2,16 Possible explanations for underreport have been proposed, such as elderly feeling of shame and fear of retaliation after disclosing the abuse to the authorities, 6,14,17,18 lack of elderly knowledge on how to do it 6 or their inability to communicate, due to mental disability or other, 6,18 this corresponding to 47.2% of our sample. Another explanation would be fear of reprisal and criminal consequences experienced by nursing homes' staff when admitting an abusive behaviour or denunciating one perpetrated by their co-workers.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation would be fear of reprisal and criminal consequences experienced by nursing homes' staff when admitting an abusive behaviour or denunciating one perpetrated by their co-workers. 6 At this level, it might be pertinent to ensure the existence of policies that guarantee staff's and elder's protection in case of report. Lack of available information to the population and specific training for professionals, resulting in uncertainty on defining criteria, low index of suspicion and/or divergent tolerance levels regarding what constitutes elder abuse, might also explain the difficulty in recognising and reporting possible abusive situations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations